Islamic Values in Spatial Function of Javanese Traditional Architecture - Supriyanta, Supriyanta; Malik, Ibrahim (Journal of Islamic Architecture, 2015)
Learn from the past is important thing as based for the next step. Learn past architecture to gain positive values can be used as guidelines to design better architectural works. Javanese traditional architecture is one of local architecture from the past which has positive values, even if it is done deeper study; it has Islamic values which can be used as principles in the process of Islamic architectural design. To achieve Islamic values in spatial pattern Javanese traditional architecture can be done through exploration and reviewing Javanese traditional architectural space afterward it is associated with Islamic values which are relevant with Al Qur’an and sunnah prophet. In fact is the spatial pattern in Javanese traditional architecture arrayed with beauty and also has Islamic valuable function. Those Islamic values are 1) high esteem guest (pendopo) through providing wide and comfortable living room; 2) create divider (pringgitan) which separate between living room and main room so that the privation can be kept; 3) separation the bed room (gandok kiwo and gandok tengen) between parents and their children who are going mature and also between boys and girls; 4) provide praying room (senthong tengah) to pray as family education and also as a place to pray to the God.